Diabetes care management patterns before and after a cancer diagnosis: A SEER‐Medicare matched cohort study. Issue 8 (30th January 2020) - Pinheiro, Laura C.; Soroka, Orysya; Kern, Lisa M.; Leonard, John P.; Safford, Monika M.
Abstract : Background: Diabetes places patients with cancer at an increased risk of infections, hospitalizations, and mortality. The objective of the current study was to characterize diabetes care management patterns among patients with cancer in the year before and, separately, after cancer diagnosis. The authors hypothesized that diabetes care declines after a diagnosis of cancer. Methods: The Surveillance, Epidemiology, and End Results (SEER) cancer registry linked to Medicare claims data was used. The authors included diabetic beneficiaries aged ≥65 years who were diagnosed with incident, nonmetastatic breast, prostate, or colorectal cancer between 2008 and 2013. Controls were diabetic Medicare beneficiaries in SEER regions who did not have cancer. Cases were matched to controls based on age, sex, Charlson Comorbidity Index, and diabetes severity. Primary outcomes were diabetes care received over 12 months: 1) hemoglobin A1c testing; 2) eye examination; and 3) low‐density lipoprotein testing. Using a difference‐in‐difference (DID) approach, the authors examined use differences 12 months before to after diagnosis for patients with cancer and controls. To avoid capturing testing related to diagnosis and not diabetes management, the authors implemented a 90‐day washout period (45 days before and/or after diagnosis). Results: A total of 32, 728 diabetic patients with cancer and 32, 728 matched noncancer controls were included. After diagnosis, patients with cancer were found to have modest, but significantly lower, rates of diabetes care use compared with controls. Patients with cancer had greater declines in hemoglobin A1c testing (DID, 2.4%; 95% CI, 1.7%‐3.0%), low‐density lipoprotein testing (DID, 4.3%; 95% CI, 3.6%‐5.0%), and receipt of all diabetes indicators (DID, 2.7%; 95% CI, 1.8%‐3.5%) 12 months before to after diagnosis. Conclusions: Compared with controls, less diabetes care use was observed among patients with cancer in the year after diagnosis. Understanding and addressing the reasons for this may improve outcomes in this population. Abstract : Herein, the authors report less use of diabetes care among patients with cancer in the year after their cancer diagnosis compared with noncancer controls. Understanding and addressing the reasons for this may improve cancer and diabetes outcomes in this population.